2012
DOI: 10.1089/jwh.2011.3248
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Risk Factors for Peripartum Transfusion

Abstract: Potentially modifiable factors most strongly associated with risk for transfusion were antenatal anemia and cesarean delivery, and their co-occurrence was synergistic. Anemia is an easily identified and treatable risk factor and warrants focus as part of preconception and interconception care in childbearing women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 25 publications
6
27
0
Order By: Relevance
“…Similar to other studies, we found increased risk of transfusion associated with bleeding and platelet disorders,(26) placenta previa, (15,27) antepartum hemorrhage,(10, 15) multiple births,(28) primparous women,(10, 27, 28) large birthweight, (10,28) and maternal hypertension. (10,15) Vaginal birth after cesarean carried a higher risk of transfusion than repeat cesarean.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Similar to other studies, we found increased risk of transfusion associated with bleeding and platelet disorders,(26) placenta previa, (15,27) antepartum hemorrhage,(10, 15) multiple births,(28) primparous women,(10, 27, 28) large birthweight, (10,28) and maternal hypertension. (10,15) Vaginal birth after cesarean carried a higher risk of transfusion than repeat cesarean.…”
Section: Discussionsupporting
confidence: 90%
“…There were higher transfusion rates following forceps deliveries than vacuum deliveries, and higher rates following intrapartum than pre-labor cesarean sections. Cesarean section had higher risk of transfusion than non-instrumental vaginal delivery, as has been reported elsewhere, (10,15,27) with this risk increased if the cesarean section was performed after the onset of labor. A Danish study, however, found that planned cesarean section had a lower risk of transfusion than a planned vaginal birth, although the 'planned vaginal birth' group included women who had instrumental births and intrapartum cesarean sections.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…There is a need for studies exploring the prevalence of anemia and predisposing risk factors for anemia observed at the time of delivery. Pregnant women with anemia, those going into labor and delivery, have the highest potential to encounter complications related to anemia and transfusion (6)(7)(8). A modest blood loss at delivery may not impair the hemodynamic response of women with normal hemoglobin levels but may be too hazardous for anemic women (5,7,9).…”
Section: Introductionmentioning
confidence: 99%
“…According to Ehranthol & Rouse et al laboring women who are anemic they are at risk and have highest potential to encounter complications related to anemia and transfusion. 8,9 Women with normal hemoglobin level are less likely to encounter serious consequences as compared to anemic women. Adebess OY, Jansen & Al-Ziqi et al also found that the average blood loss that occurs at delivery will not affect a women with normal hemoglobin levels.…”
Section: Introductionmentioning
confidence: 99%